Skene gland cyst in post puberal girl - Antonella Centonze; Domenico Salerno; Stellario Capillo; Aurelio Mazzei; Giuseppe Stranieri (Elsevier, 2019)
The finding of an interlabial mass in a girl can create doubts in relation to its etiology, its implications and its management.Skene cysts are an unusually rare at any age, but especially in a girl in post-pubertal age as well as in adult women.Because these lesions can simulate other lesions with important clinical implications, careful urological evaluation is required.Several paraurethral glands are described, Skene's glands are the largest and are located on the distal urethral floor.The incidence of Skene cysts is probably much higher than estimated due to a lack of systematic reporting of their finding.We performed a literature evaluation regarding the reporting of Skene cysts in children and adults.We report the case of a voluminous interlabial mass found in a girl in post-puberal age, the characteristic displacement of the urethral meatus confirmed the suspicion of Skene's parauthral cyst.Skene cysts management tends to be conservative when seen in the newborn, while a surgical approach in the young adult is preferable.